CLASSIFICATION OF MOVEMENT GAMES FOR PRIMARY SCHOOL AGE AND PRIMARY ADOLESCENTS - Bakhram Pulatovich Pardayev (Proximus Journal Publishing, 2025)
The article classifies active games intended for primary school and younger adolescents. The practice of educating the younger generation in our country testifies to the fact that games are one of the most important means of forming high moral and physical qualities in children and adolescents. It plays a particularly important role in the physical education of school-age children, as it contributes to the preservation and strengthening of health, the normalization of physical development, and the comprehensive improvement of motor skills.
Keywords: adolescents; leader; players; educational